On Efficient Method for System of Fractional Differential Equations. (9th March 2011) - Khan, Najeeb Alam; Jamil, Muhammad; Ara, Asmat; Khan, Nasir-Uddin
Abstract : The present study introduces a new version of homotopy perturbation method for the solution of system of fractional-order differential equations. In this approach, the solution is considered as a Taylor series expansion that converges rapidly to the nonlinear problem. The systems include fractional-order stiff system, the fractional-order Genesio system, and the fractional-order matrix Riccati-type differential equation. The new approximate analytical procedure depends only on two components. Comparing the methodology with some known techniques shows that the present method is relatively easy, less computational, and highly accurate.